Blood flow velocity in the extraocular vessels in chronic smokers. Issue 2 (1st February 1997) - Kaiser, Hedwig J; Schoetzau, Andreas; Flammer, Josef
Abstract : AIMS: To determine blood flow velocity in the extraocular vessels in healthy, chronic smokers and to compare these blood flow velocities with those of healthy non-smokers. METHODS: In 46 healthy chronic smokers and 189 healthy non-smokers, peak systolic velocity (PSV), end diastolic velocity (EDV), and the resistivity index (RI) were measured in the ophthalmic artery (OA), central retinal artery (CRA), lateral short posterior ciliary artery (LPCA), and medial short posterior ciliary artery (MPCA) by means of a colour Doppler device, Siemens Quantum 2000.The maximal (max) and minimal (min) velocities were measured in the central retinal vein (CRV). Only one eye was measured in each subject, and right and left eyes were chosen randomly. Blood flow velocities were compared with one way MANOVA and t tests. The influence of age, sex, systolic and diastolic blood pressure, as well as heart rate on blood flow velocity and RI were evaluated by an analysis of covariance. The potential differences of the influence of the covariables on blood flow variables in smokers and non-smokers were tested by calculating the interactions. RESULTS: In the majority of measured vessels blood flow velocity was higher in smokers than in non-smokers. This difference was statistically significant in the OA, CRV, and LPCA. The RI indices were equal or slightly lower in smokers. Furthermore, smokers had significantly lower systolic and diastolic blood pressure. Heart rate was higher in smokers but this difference did not reach statistical significance. CONCLUSIONS: Colour Doppler measurements may differ significantly in smokers compared with non-smokers. Therefore, smoking habits should be considered when interpreting colour Doppler imaging results, and comparing different groups of diseased or healthy subjects.